Pendidikan karakter mahasiswa berbasis epistemologi islam: Integrasi spiritualitas dan rasionalitas - farhan, rama aditya (Maliki Interdisciplinary Journal, 2025)
Character education is the main foundation in creating student character with integrity and morals. For this reason, it is very important to unite the aspects of spirituality and rationality in the character formation procces. The researcher used a literature study model with critical analysis, the results of the research study show that the formation of student character can be carried out through islamic epistemology which is the basic foundation. The integration of spiritual and rational values encourages the creation of students who excel intellectually and morally. This study recommends the development of a relevant educational curriculum by integrating spiritual and rational values in higher education. The study empahasizes the importance of every student having good behaviors such as love, tolerance, brotherhood, and mutual respect. Therefore, to ensure that every student can practice good character, continuous training is needed. The goal is to ensure that students understand the character education teachings that have been applied in the campus environment and are able to implement them in their daily lives.